Optical microscopy – how small can it go?. (November 2020) - Demming, Anna
Abstract : For centuries diffraction limited the resolution of optical microscopy. The past 50 years have, however, seen one limitation after another buckle under the ingenuity of a host of wide-ranging techniques, from lenses to tips, chips and doughnuts. Anna Demming reports